A randomised comparison of single-incision versus traditional transobturator midurethral sling in women with stress urinary incontinence: results of a 24-month follow-up. Issue 6 (June 2016) - Schellart, René; Rengerink, Katrien; Aa, Frank; Lucot, Jean-Philippe; Kimpe, Bart; Dijkgraaf, Marcel; Roovers, Jan-Paul
Abstract Introduction and hypothesis Midurethral sling procedures have become the principal surgical treatment for women with stress urinary incontinence (SUI). The 1-year results of this international trial comparing the efficacy and morbidity of a single-incision midurethral sling (SIMS; MiniArc) and a transobturator standard midurethral sling (SMUS; Monarc) showed that MiniArc is non-inferior regarding subjective cure and superior with regard to postoperative pain and recovery. The objective was to compare subjective and objective cure, morbidity and surgery-related discomfort following SIMS and transobturator SMUS up to a 24-month follow-up. Methods We carried out a non-blinded, randomised, controlled trial. Women with symptomatic SUI were eligible. Primary outcome was subjective cure, defined as an improvement on the Patient Global Impression of Improvement (PGI-I), at 12, 24 and 36 months. Secondary outcomes were objective cure based on the cough stress test, disease-specific quality of life questionnaires, surgical parameters and physical performance during recovery. Analysis was by intent to treat. Differences between the two groups regarding dichotomous variables were Chi-squared tested and presented as relative risks (RR) with corresponding 95 % confidence intervals. Results We randomised 97 women to MiniArc and 96 to Monarc. At the 24-month follow-up, subjective cure was 84 % following MiniArc and 89 % following Monarc (RR −5; 95% CI −0.17 to 0.06). Objective cure was 93 % following MiniArc and 94 % following Monarc (RR −1; 95% CI −0.10 to 0.07). Both procedures have low complication rates. Conclusions At the 2-year follow-up, the non-prespecified analysis of this randomised trial showed that the MiniArc, a single-incision sling, had similar subjective and similar objective cure rates, although non-inferiority to Monarc for subjective cure could not be demonstrated.